Cloning: A Technofeminist Narrative of Posthumanism on Tomie's Character in Anime Junji Ito Collection (2018) - Aqiilah Bilqiis Salsabiil Harahap; Sri Kusumo Habsari; Deny Tri Ardianto (Journal of Anime and Manga Studies, 2024)
This study examines the shifting meaning of subjectivity and the blurred boundaries between humans and nonhumans. Additionally, it explores the impact of technology intervention on gender, drawing from the principles of posthumanism philosophy. Cloning is one of the issues highlighted in the posthuman realm. This study seeks to examine the incorporation of posthumanism and technofeminism in the character Tomie in the anime Junji Ito Collection (2018, Itô Junji "Korekushon"), with the intention of challenging the sexualization of shôjo while remaining skeptical using the narrative analysis method. The results and findings show that Tomie presents a posthuman idea centered on her super regeneration ability and cloned creations to defy the limits of humanity. This idea also promotes elements of technofeminism that lead to the use of biotechnology related to reproduction. Nevertheless, in the end, Ito tries to invite the audience to remain critical in responding to the issue of technofeminism, both in terms of ethics and objectivity.